Electrochemical Sensor for Detection of Glucose Based on Ni@Pt Core‐shell Nanoparticles Supported on Carbon. Issue 4 (12th October 2015) - Mei, He; Wu, Wenqin; Yu, Beibei; Wu, Huimin; Wang, Shengfu; Zhang, Xiuhua; Xia, Qinghua
Abstract: In this work, Ni@Pt core‐shell nanoparticles with diameter of 3–4 nm and thin Pt shell was synthesized by a successive reduction approach using carbon as support to develop high‐performance non‐enzymatic glucose sensor. The resulting electrochemical sensor displayed good catalytic activity toward glucose oxidation, presenting a high current density of 66.9 µA mM −1  cm −2 at an applied potential of −0.1 V. It showed a wide linear range of 0.1–30.1 mM and the limit of detection was down to 30 µM ( S / N =3). Notably, it was found that the proposed sensor exhibited good selectivity to avoid the interference from ascorbic acid, uric acid, fructose and acetamidophenol. Furthermore, the feasibility of the as‐prepared non‐enzymatic glucose sensor in the determination of glucose in serum samples was successfully implemented. Abstract :